(untitled) (Research, Society and Development, 2023)
The objective of this study is to determine the incidence of self-medication in university students, highlighting its main causes. It was necessary to carry out a collection in PubMed and LILACS, using the descriptors, self-medication, university students and risks. After refining the search and applying the inclusion criteria, this review compiled 11 articles that referred to the subject of this study. it was observed that the causes related to the incorrect practice of medicines, among university students, are enormous, especially in academics in the area of ​​health sciences. Therefore, students’ knowledge about the risks of self-medication may be related to the knowledge acquired during training. However, this factor is very worrying, since most of them, despite knowing the risks, are supporters of the practice. It points to the need to strengthen the education of university students, especially in the area of ​​health sciences, with regard to the rational use of medicines.